Insights into the phylogenetic diversity, biological activities, and biosynthetic potential of mangrove rhizosphere Actinobacteria from Hainan Island - Ye, Jing-jing; Zou, Ren-jian; Zhou, Dong-dong; Deng, Xiao-lin; Wu, Ni-lin; Chen, Dan-dan; Xu, Jing (Frontiers in Microbiology, 2023)
Mangrove rhizosphere soils host diverse Actinobacteria tolerant to numerous stresses and are inevitably capable of exhibiting excellent biological activity by producing impressive numbers of bioactive natural products, including those with potential medicinal applications. In this study, we applied an integrated strategy of combining phylogenetic diversity, biological activities, and biosynthetic gene clusters (BGCs) screening approach to investigate the biotechnological importance of Actinobacteria isolated from mangrove rhizosphere soils from Hainan Island. The actinobacterial isolates were identifified using a combination of colony morphological characteristics and 16S rRNA gene sequence analysis. Based on the results of PCR-detected BGCs screening, type I and II polyketide synthase (PKS) and non-ribosomal synthetase (NRPS) genes were detected. Crude extracts of 87 representative isolates were subjected to antimicrobial evaluation by determining the minimum inhibitory concentration of each strain against six indicator microorganisms, anticancer activities were determined on human cancer cell lines HepG2, HeLa, and HCT-116 using an MTT colorimetric assay, and immunosuppressive activities against the proliferation of Con A-induced T murine splenic lymphocytes in vitro. A total of 287 actinobacterial isolates affiliated to 10 genera in eight families of six orders were isolated from five different mangrove rhizosphere soil samples, specififically, Streptomyces (68.29%) and Micromonospora (16.03%), of which 87 representative strains were selected for phylogenetic analysis. The crude extracts of 39 isolates (44.83%) showed antimicrobial activity against at least one of the six tested indicator pathogens, especially ethyl acetate extracts of A-30 (Streptomyces parvulus), which could inhibit the growth of six microbes with MIC values reaching 7.8 μg/mL against Staphylococcus aureus and its resistant strain, compared to the clinical antibiotic ciproflfloxacin. Furthermore, 79 crude extracts (90.80%) and 48 (55.17%) of the isolates displayed anticancer and immunosuppressive activities, respectively. Besides, four rare strains exhibited potent immunosuppressive activity against the proliferation of Con A-induced T murine splenic lymphocyte in vitro with an inhibition rate over 60% at 10 μg/mL. Type I and II polyketide synthase (PKS) and non-ribosomal synthetase (NRPS) genes were detected in 49.43, 66.67, and 88.51% of the 87 Actinobacteria, respectively. Signifificantly, these strains (26 isolates, 29.89%) harbored PKS I, PKS II, and NRPS genes in their genomes. Nevertheless, their bioactivity is independent of BGCs in this study. Our findings highlighted the antimicrobial, immunosuppressive, and anticancer potential of mangrove rhizosphere Actinobacteria from Hainan Island and the biosynthetic prospects of exploiting the corresponding bioactive natural product.